Dementia and vagotomy in Taiwan: a population-based cohort study. Issue 3 (30th March 2018) - Lin, Shih-Yi; Lin, Cheng-Li; Wang, I-Kuan; Lin, Cheng-Chieh; Lin, Chih-Hsueh; Hsu, Wu-Huei; Kao, Chia-Hung
Abstract : Objective: Truncal vagotomy is associated with a decreased risk of subsequent Parkinson disease (PD), although the effect of vagotomy on dementia is unclear. In response, we investigated the risk of dementia in patients who underwent vagotomy. Setting: Population-based cohort study. Participants: A total of 155 944 patients who underwent vagotomy (vagotomy cohort) and 155 944 age-matched, sex-matched and comorbidity-matched controls (non-vagotomy cohort) were identified between 2000 and 2011. Primary and secondary outcome measures: All patient data were tracked until the diagnosis of dementia, death or the end of 2011. The cumulative incidence of subsequent dementia and HRs were calculated. Results: The mean ages of the study patients in the vagotomy and non-vagotomy cohorts were 56.6±17.4 and 56.7±17.3 years, respectively. The overall incidence density rate for dementia was similar in the vagotomy and non-vagotomy cohorts (2.43 and 2.84 per 1000 person-years, respectively). After adjustment for age, sex and comorbidities such as diabetes, hypertension, hyperlipidaemia, stroke, depression, coronary artery disease and PD, the patients in the vagotomy cohort were determined to not be at a higher risk of dementia than those in the non-vagotomy cohort (adjusted HR=1.09, 95% CI 0.87 to 1.36). Moreover, the patients who underwent truncal vagotomy were not associated with risk of dementia (adjusted HR=1.04, 95% CI 0.87 to 1.25), compared with the patients who did not undergo vagotomy. Conclusion: Vagotomy, either truncal or selective, is not associated with risk of dementia.